Analysis of the Effect of Utilization of Science and Technology, Human Resources and Asset Land Management on Sustainable Optimization - Ita Risna; Harsuko Riniwati; Nila Nuzula; Bunga Hidayati (Postgraduate, University of Mataram, 2024)
Natural resources, especially land, are finite resources that constrain development. The limited availability of land in urban areas is disproportionate to the growing demand. This land is important for developing city infrastructure, such as office buildings, housing, education, health services, parks, and green open spaces, as well as other functions that support city infrastructure. The research was conducted as an effort to support government programs towards the optimization of sustainable cities by looking at the propositions of each variable. The product of this research helps the government optimize the development of sustainable cities. Testing with quantitative methods using partial least square data analysis utilizing Smart-PLS software. The results showed that the science and technology variable had an insignificant effect on the sustainable optimization of land assets in Malang City. However, the human resources variable and the asset land variable have a significant positive effect on the sustainable optimization of asset land in Malang City. The conclusion of this study shows that science and technology does not have a direct impact on the optimization of sustainable land assets in Malang City, but has a significant positive influence through the mediation of human resources. Therefore, researchers recommend improving science and technology in land asset management through improving the education and skills of human resources in the Malang City government.